OPTIMALISASI PENGEMBANGAN PERENCANAAN PERKULIAHAN DARING MATA KULIAH BAHASA INDONESIA UNIVERSITAS TJUT NYAK DHIEN MEDAN - Dila Handayani; Fitry Wahyuni (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The purpose of this research is to optimize it by developing recovery planning starting from Lecture Contracts, SAP and RPS, Evaluation and Digital Book Teaching Materials in Indonesian Language courses. This type of research is research and development. The research and development steps are guided by the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results of the Validator Review of Learning Planning Experts for Online Lectures for Indonesian Language Courses at Tjut Nyak Dhien University stage 1, for lecture contracts, SAP & RPS and Evaluation, the number is 33 with a percentage of 76.7% and the category is feasible. Review of the Validator of Learning Planning Online Lectures for Indonesian Language Course at Tjut Nyak Dhien University phase 2, for lecture control, SAP, RPS and Evaluation the total is 43 with a percentage of 100% and the category is very feasible. Digital book validation research on Optimizing the Development of Online Lecture Learning Planning for Indonesian Language Courses at Tjut Nyak Dhien University is 80.5%. The results obtained on the results of student lectures from several meetings obtained an increase in UTS scores with a percentage of 94%. The conclusion of the research results obtained are the results of expert validation of Lecture Contracts, SAP, RPS, Evaluation and Digital Book Teaching Materials that are suitable for use in Optimizing the Development of Learning Planning for Online Lectures for Indonesian Language Courses at Tjut Nyak Dhien University.Keywords: Optimization, Development, Planning, Online, Indonesian